Assessment of education program based on the salutogenic theory on fear of childbirth and choice of birth method among nulliparous women: A randomized controlled trial - Safieh Kananikandeh; Farkhondeh Amin Shokravi; Mojgan Mirghafourvand; Shayesteh Jahanfar (Heliyon)
Background: Fear of childbirth significantly affects nulliparous women and can have repercussions for both mothers and children. Drawing on evidence, the salutogenic theory has been proposed as a framework to address and manage this fear. Aim: Thia study aimed to assess the efficacy of an educational program grounded in the salutogenic theory in mitigating fear of childbirth and influencing the choice of birth method among nulliparous women. Design: A randomized clinical trial was used. Participant/setting: This study involved 63 nulliparous women attending health centers in Bostanabad city in East Azerbaijan Province, Iran. Methods: This intervention comprised four group sessions lasting 30–45 min each, guided by the principles of the salutogenic theory. Participants were randomly assigned to either the intervention or control group. Data were collected through self-reports using the Wijma Delivery Expectancy/Experience Questionnaire, Antonovsky's Sense of Coherence scale, and a birth method choice checklist. The analysis involved independent sample t-tests, ANCOVA, repeated measures tests, chi-square tests, Cochran's Q tests, and SPSS 27 software. Results: In the intervention group, the mean score for childbirth fear significantly decreased (MD= 10.10, 95 % CI= 1.88–18.31), and the sense of coherence mean score was higher compared to the control group (MD= 9.10, 95 % CI= 1.71–16.49). However, the frequency of choosing vaginal birth remained consistent post-intervention. Conclusions: An intervention grounded in the salutogenic theory proved effective in assisting nulliparous women in realizing their chosen birth method by addressing fear and enhancing their sense of coherence. Trial registration: IRCT20210506051202N1. The trial registration date was 22/08/2021.